Fundless Loan Agreement - L. B. Gudovicheva (Сибирское юридическое обозрение, 2020)
The concept of fundless loan has been the object of a lot of attention in judicial practice: almost no lawsuit to recover a borrowed amount is complete without a debtor's statement about the fundless loan. However, in doctrinal literature most often this concept is mentioned in passing to illustrate other concepts and categories or to give diversity to scientific or scientific-practical work. It should be recognized that the fundless loan is a phenomenon exclusively of Russian law. However, neither scholars nor practitioners put forward proposals to exclude non-monetary assets as a legal construct from existing legislation. It seems that this is due to the essence of this legal phenomenon, which received its name in the Civil Code of the Russian Federation. These norms should be attributed to the category of procedural norms that link the substantive regulation of recognition of a contract as non-concluded exclusively in a judicial proceeding. The court does not have the right to evade consideration of the application for a fundless loan, but at the same time it cannot raise this issue on its own initiative. However, the prohibition to discuss this issue by the court does not contain either substantive or procedural legislation. In some cases, the application of the adversarial principle of the parties to the dispute may be limited.